Maslahah Study of an Innovation Program Called "Always Samawa Forward" For New Bride - Hidayat, Rahmat; Hadi, Sutrisno; Tiswarni, Tiswarni; Bakhtiar bin Jelani, Ahmad (Nurani, 2022)
The purpose of this study was to examine an innovative program called "Always Samawa Forward" which was initiated by the Department of Population and Civil Registration (Disdukcapil), South Solok Regency, from the perspective of maslaḥah. The research was motivated by the efforts made by the Disdukcapil in responding the complaints from the community who find it difficult to process various new residence documents when they are married. This research is qualitative. Data sources are primary and secondary. Primary data comes from interviews with Disdukcapil employees, Head of KUA, Ulama, Head of Jorong, and several communities in South Solok Regency. Data collection techniques are interviews, and documentation. data analysis is descriptive. The results of the study show that this innovation program is very important to do considering the difficulties that must be faced by newlyweds and their families in managing some of their residence documents after marriage. The Mechanism of the program begins with the MoU between Disdukcapil and the heads of KUA in South Solok. From the perspective of maslaḥah, this innovation program is appropriate because it makes it easier for newly married couples and their families to manage various new population documents. When viewed from the level of maslaḥah, the policy of this innovation program can be classified as maslaḥah hajiyah.